Asante Calcium Green and Asante Calcium Red--novel calcium indicators for two-photon fluorescence lifetime imaging. - Karolina Jahn; Carsten Hille (PLoS ONE, 2014)
For a comprehensive understanding of cellular processes and potential dysfunctions therein, an analysis of the ubiquitous intracellular second messenger calcium is of particular interest. This study examined the suitability of the novel Ca2+-sensitive fluorescent dyes Asante Calcium Red (ACR) and Asante Calcium Green (ACG) for two-photon (2P)-excited time-resolved fluorescence measurements. Both dyes displayed sufficient 2P fluorescence excitation in a range of 720-900 nm. In vitro, ACR and ACG exhibited a biexponential fluorescence decay behavior and the two decay time components in the ns-range could be attributed to the Ca(2+)-free and Ca(2+)-bound dye species. The amplitude-weighted average fluorescence decay time changed in a Ca(2+)-dependent way, unraveling in vitro dissociation constants K(D) of 114 nM and 15 nM for ACR and ACG, respectively. In the presence of bovine serum albumin, the absorption and steady-state fluorescence behavior of ACR was altered and its biexponential fluorescence decay showed about 5-times longer decay time components indicating dye-protein interactions. Since no ester derivative of ACG was commercially available, only ACR was evaluated for 2P-excited fluorescence lifetime imaging microscopy (2P-FLIM) in living cells of American cockroach salivary glands. In living cells, ACR also exhibited a biexponential fluorescence decay with clearly resolvable short (0.56 ns) and long (2.44 ns) decay time components attributable to the Ca(2+)-free and Ca(2+)-bound ACR species. From the amplitude-weighted average fluorescence decay times, an in situ K(D) of 180 nM was determined. Thus, quantitative [Ca(2+)]i recordings were realized, unraveling a reversible dopamine-induced [Ca(2+)]i elevation from 21 nM to 590 nM in salivary duct cells. It was concluded that ACR is a promising new Ca(2+) indicator dye for 2P-FLIM recordings applicable in diverse biological systems.